The mysterious Benedict Society - Stewart, Trenton Lee.; Ellis, Carson, 1975- (New York : Little, Brown, 2007)
After passing a series of mind-bending tests, four children are selected for a secret mission that requires them to go undercover at the Learning Institute for the Very Enlightened, where the only rule is that there are no rules.
Keywords: Adventure and adventurers -- Fiction; Schools -- Fiction; Science fiction